Objective analysis of wind field over Indian region by optimum interpolation method - RAJAMANI, S.; TALWALKAR, D. R.; RAY, S. P.; UPASANI, P. U. (MAUSAM, 1983)
A scheme for objective analysis of wind field over Indian region was drawn up using optimum interpolation method. For this the autocorrelation functions and the structure functions of the wind field over India have been computed for 850, 700 and 500 mb levels. These statistical structure functions were used in calculating the weighting factors for the observing stations with respect to the given grid point and objective analyses were made at 850 and 700 mb levels for eight days from 24 July to 31 July 1969. In order to evaluate the objective analyses quantitatively RMS errors were computed by interpolating the winds at the observing stations from the objectively analysed field and comparing with actually observed winds, Also, centres of the monsoon system obtained in objective analyses were compared with those in subjective analyses.